Leptospirosis Relative Risk Estimates based on Continuous-Time, Discrete-Space Stochastic SIR-L-SI Transmission Model - Nor Azah Samot @ Samat (Tanjung Malim, 2024)
Leptospirosis Relative Risk Estimates based on Continuous-Time, Discrete-Space Stochastic SIR-L-SI Transmission Model by Nor Azah Samot @ Samat